Optical Fiber Communication Conference (OFC) 2020 2020
DOI: 10.1364/ofc.2020.m3z.9
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Software-Defined Packet-Optical Network Emulation with Mininet-Optical and ONOS

Abstract: We demonstrate practical software emulation of a software-defined, packetoptical network. Our emulator, Mininet-Optical, models the physical, data plane and control plane behavior, under control of the ONOS SDN controller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…There are specific challenges that sprout with the implementation of orchestration for SDNs. From the reviews under [132], in terms of optical network flexibility, most researchers adapted to using a reconfigurable optical add/drop multiplexer (ROADM) [133] as an essential component where SDN functionality can be deployed into the optical network environment [134]. It could also be inferred that the ROADM component [135] being vendor -neutral allows for a wide variety and accommodates a wide range of proposed algorithms [136], which can be used.…”
Section: Security and Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are specific challenges that sprout with the implementation of orchestration for SDNs. From the reviews under [132], in terms of optical network flexibility, most researchers adapted to using a reconfigurable optical add/drop multiplexer (ROADM) [133] as an essential component where SDN functionality can be deployed into the optical network environment [134]. It could also be inferred that the ROADM component [135] being vendor -neutral allows for a wide variety and accommodates a wide range of proposed algorithms [136], which can be used.…”
Section: Security and Reliabilitymentioning
confidence: 99%
“…• Adapting to advance learning techniques: Since the optical network is associated with the physical layer, on some occasions, some network specifications like the "baud rate" as well as "modulation formats affect the transmission line quality. This means that it is crucial that SDON adapts to some network modelling algorithms to be able to predict the transmission quality [164]. A few of the researchers in the review suggested Dijkstra algorithm and some machine learning techniques.…”
Section: Recommendations and Future Research Directionsmentioning
confidence: 99%
“…Finally, it is also worthwhile mentioning comparable initiatives to our proposal such as the software-defined packet-optical network emulator [34], which is based on an optical extension of the popular packed-oriented network emulator Mininet [35]. Relevantly, ref.…”
Section: State Of the Artmentioning
confidence: 99%
“…Relevantly, ref. [34] proposes a software suite capable of emulating optical-layer QoT performances such as OSNR, gOSNR and BER, and report its impact to the SDN controller. This emulation is based on augmenting packet in traditional Mininet instances with wavelength/channel information, which is used in modified instances of Open vSwitch.…”
Section: State Of the Artmentioning
confidence: 99%
“…A significant advantage of extending SDN to photonic networks is the combined dynamic service provisioning and optimization by the SDN controller because of its global knowledge of several network layers. A recent work [9] provides an SDN-controlled platform to simulate end-to-end integrated data plane of packet and optical network. The physical behaviour of a WDM network is simulated using analytical models and an optical data plane is emulated as data packets with additional information about wavelength.…”
Section: Introductionmentioning
confidence: 99%